Dynamic Spectrum Management From Cognitive Radio to Blockchain and Artificial Intelligence - Liang, Ying-Chang (Signals and Communication Technology,, 2020)
This open access book, authored by a world-leading researcher in this field, describes fundamentals of dynamic spectrum management, provides a systematic overview on the enabling technologies covering cognitive radio, blockchain, and artificial intelligence, and offers valuable guidance for designing advanced wireless communications systems. This book is intended for a broad range of readers, including students and professionals in this field, as well as radio spectrum policy makers.